2018
DOI: 10.14419/ijet.v7i4.36.25374
|View full text |Cite
|
Sign up to set email alerts
|

Populus Tremula Plants with Reduced Expression of the 4-Coumarate-CoA Ligase Gene Demonstrate Defects of the Rhizogenesis

Abstract: Changing expression of a single gene by introducing mutations or transformation often affects expression of other genes, which results in the modification of the plant phenotype. We have obtained aspen plants with reduced expression levels of 4CL gene (4-coumarate-CoA ligase). Change in qualitative composition and 11-23% reduced lignin content were observed in the wood of the greenhouse plants. In the study of rhizogenesis in vitro it was found that the micro shoots of transgenic plants formed a greater number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The RT-qPCR method and the analysis of the obtained data were described in detail in Kovalitskaya et al [50]. Actin and ubiquitin were used as reference genes in the study presented here.…”
Section: Real-time Quantitative Pcr (Rt-qpcr) Analysismentioning
confidence: 99%
“…The RT-qPCR method and the analysis of the obtained data were described in detail in Kovalitskaya et al [50]. Actin and ubiquitin were used as reference genes in the study presented here.…”
Section: Real-time Quantitative Pcr (Rt-qpcr) Analysismentioning
confidence: 99%
“…RNA interference-mediated down-regulation of the 4-coumarate: coenzyme A ligase in Populus tremula alters lignification and plant growth [356] and rhizogenesis [357]. Metabolomic studies of these plants revealed strong changes in the biosynthesis of phenolic compounds, in particular the accumulation of glycosylated forms, which may indicate their cytotoxicity.…”
Section: Transgenic Trees and Allelopathymentioning
confidence: 99%